Visual identity design of the Batik Ciprat Giyanta SMEs in Banjarnegara - Kusumohendrarto, Raden Hadapiningrani; Fitriyandani, Yanuar Maulana (Universitas Negeri Yogyakarta, 2024)
Batik is an indigenous Indonesian cultural heritage that continues to be preserved. Numerous patterns and techniques for making batik have been developed, including Batik Ciprat (splash technique batik). Giyanta is one of the Batik Ciprat production houses located in Banjarnegara. In the batik business, Giyanta's visual identity is currently insufficiently informative and appealing, resulting in suboptimal promotional activities. This study employs an analysis and design process as part of this practice-based research. Data was collected through interviews and field observations, forming the basis for concept development and guiding visual identity design. The design process involved SWOT analysis, target audience identification, referencing, brainstorming, alternative logo design, final logo selection and its philosophy, colour and typography decisions, and supporting elements. This design aims to enhance the brand value and image of the Batik Ciprat Giyanta SME in the public's perception.